Analysis of Porcine Model of Fecal-Induced Peritonitis Reveals the Tropism of Blood Microbiome - Hyun, Hwi; Lee, Min Seok; Park, Inwon; Ko, Hwa Soo; Yun, Seongmin; Jang, Dong-Hyun; Kim, Seonghye; Kim, Hajin; Kang, Joo H.; Lee, Jae Hyuk; Kwon, Taejoon (Frontiers in Cellular and Infection Microbiology, 2021)
Recent studies have suggested the existence of a blood microbiome in the healthy host. However, changes in the blood microbiome upon bloodstream infection are not known. Here, we analyzed the dynamics of the blood microbiome in a porcine model of polymicrobial bacteremia induced by fecal peritonitis. Surprisingly, we detected bacterial populations in the bloodstream even before the infection, and these populations were maintained over time. The native blood microbiome was notably taxonomically different from the fecal microbiome that was used to induce peritonitis, reflecting microbial tropism for the blood. Although the population composition after the infection was similar to that of the native blood microbiome, new bacterial strains entered the bloodstream upon peritonitis induction as clinical symptoms relevant to sepsis developed. This indicates that the bacteria detected in the blood before peritonitis induction were derived from the blood rather than a contamination. Comparison of the functional pathways enriched in the blood and fecal microbiomes revealed that communication and stress management pathways are essential for the survival of the blood microbiome.